Validating controlled attenuation parameter in the assessment of hepatic steatosis in living liver donors - Broering, Dieter; Shawkat, Mohamed; Albenmousa, Ali; Abaalkhail, Faisal; Alabbad, Saleh; Al-Hamoudi, Waleed; Alghamdi, Saad; Alqahthani, Saleh; Jaafari, Ahmad; Troisi, Roberto; Bzeizi, Khalid (PloS one, 2021)
Hepatic steatosis (HS) negatively impacts transplant outcomes in living liver donors. To date, liver biopsy is preferred for HS evaluation. This study aims to evaluate the measurement of controlled attenuation parameter (CAP) as a diagnostic tool of HS in living liver donors. Candidates recruited to this study, conducted from April 2016 to February 2020, were potential donors who had undergone transient elastography using Fibroscan® and CAP measurements at liver segments VI and VII, followed by liver biopsy. The HS grades from liver biopsy were classified as S0 (<5%), S1 (5-33%), S2 (33-66%), and S3 (>66%). For CAP, they were S0 (≤218dB/m), S1 (218-249dB/m)), S2 (250-305dB/m)), and S3 (>305dB/m)). The CAP measurements were compared with the liver biopsy results. Of the 150 potential donors [male, 73.3%; mean age, 30.0±7.0 years; body mass index (BMI), 24.7±3.5kg/m2], 92 (61.3%) had no or mild HS, while 58 (38.7%) and 10% had moderate to severe HS based on CAP and liver biopsy, respectively. Subjects with moderate to severe HS per CAP were mostly males (0.014), and had higher BMI (p = .006), alanine aminotransferase (ALT) (.001), gamma-glutamyl transferase (.026), and high-density lipoprotein (.008). On multivariate analysis, high ALT (OR, 1.051; 95% CI, 1.016-1.087; p = .004) was a predictor of significant HS. The sensitivity, specificity, positive and negative predictive values of CAP to detect significant HS were 93.3%, 67.4, 24.1%, and 98.9%, respectively. The high sensitivity and negative predictive values of CAP make it a good screening test to exclude significant HS in potential living liver donors which, in turn, can help avoid unnecessary liver biopsies.